Vaccinium bracteatum Leaf Extract Reverses Chronic Restraint Stress-Induced Depression-Like Behavior in Mice: Regulation of Hypothalamic-Pituitary-Adrenal Axis, Serotonin Turnover Systems, and ERK/Akt Phosphorylation - Oh, Dool-Ri; Yoo, Ji-Seok; Kim, Yujin; Kang, Huwon; Lee, Hunmi; Lm, So J.; Choi, Eun-jin; Jung, Myung-A; Bae, Donghyuck; Oh, Kyo-Nyeo; Hong, Ji-Ae; Jo, Ara; et al. (Frontiers in Pharmacology, 2018)
The leaves of Vaccinium bracteatum Thunb. are a source of traditional herbal medicines found in East Asia. The present study aimed to evaluate the mechanisms underlying the antidepressant-like effects of water extract of V. bracteatum Thunb. leaves (VBLW) in a mouse model of chronic restraint stress (CRS) and to identify the possible molecular in vitro mechanisms of the neuroprotective effects. The CRS-exposed mice were orally administered VBLW (100 and 200 mg/kg) daily for 21 days consecutively. The behavioral effects of VBLW were assessed through the forced swim test (FST) and the open field test (OFT). The levels of serum corticosterone (CORT), corticotropin releasing hormone (CRH), and adrenocorticotropin hormone (ACTH), brain monoamines, such as serotonin, dopamine, and norepinephrine, and serotonin turnover by tryptophan hydroxylase 2 (TPH2), serotonin reuptake (SERT), and monoamine oxidase A (MAO-A) were evaluated, in addition to the extracellular signal-regulated kinases (ERKs)/protein kinase B (Akt) signaling pathway. CRS-exposed mice treated with VBLW (100 and 200 mg/kg) showed significantly reduced immobility time and increased swimming and climbing times in the FST, and increased locomotor activity in the OFT. Moreover, CRS mice treated with VBLW exhibited significantly decreased CORT and ACTH, but enhanced brain monoamine neurotransmitters. In addition, CRS mice treated with VBLW had dramatically decreased protein levels of MAO-A and SERT, but increased TPH2 protein levels in the hippocampus and the PFC. Similarly, VBLW significantly upregulated the ERKs/Akt signaling pathway in the hippocampus and the PFC. Furthermore, VBLW showed neuroprotective effects via increased CREB phosphorylation in CORT-induced cell injury that were mediated through the ERK/Akt/mTOR signaling pathways. These results suggested that the antidepressant-like effects of VBLW might be mediated by the regulation of the HPA axis, glucocorticoids, and serotonin turnover, such as TPH2, SERT, and MAO-A, as well as the concentration of monoamine neurotransmitters, and the activities of ERK and Akt phosphorylation, which were possibly associated with neuroprotective effects.